Bureaucracies of the "un-adoptable" - Honiball, Jessica (My University, 2019)
This thesis is concerned with the ways in which adoption bureaucracies shape and impact families within South Africa. It examines adoption experiences by conducting research across South Africa in 2017 and it argues, that the bureaucratic process involved within adoption is influencing the ways in which kinship relations are created, as the government is withholding birth certificates and classifying children as un-adoptable. It examines the impact of such classification and what it means to the families in their day to day lives. It examines the above argument, by drawing on ethnographic research to illustrate the realities of adoptive families. In addition, it argues that the government is withholding the right to live a ‘dignified’ life when they make decisions for children.
This is a dissertation submitted in partial satisfaction of the requirements for a master’s degree in Social Anthropology by Jessica Honiball at the University of Witwatersrand, 2019